Assessment of Heavy Metals in Some Ground Water Wells at Baghdad City /Iraq - Husam Saleem Khalaf (Journal of Global Pharma Technology, 2018)
Occurrence the heavy metals in water is one of the most important concerns. may cause savior health problems. In this work we made an attempt to know the quantity of six heavy metals in groundwater in different locations of Baghdad city. Examinations were made on groundwater of the review region to assess the heavy metals. Groundwater samples were gathered and analyzed utilizing Atomic Absorption Spectrophotometer for their Manganese, Iron, Zinc, Cadmium, Copper and Lead content and their levels compared with World Health Organization (WHO) specified maximum contaminant level. In order to accomplish this, water samples were obtained from 10 randomly selected wells in the region, in February and August, 2016. The study showed that the groundwater in the study area were generally alkaline (moderate) and contained Cu+2, Fe+2, Pb+2, Cd+2, Cu+2 and lead concentrations that are higher than the permissible limits suggested by the (WHO). The study can then be concluded to be contaminated with some heavy metals because of the effect of many activities in the survey area. Decreased the operation of Industrial treatment, laws and the integrated management led to deteriorating the groundwater quality. Also the study inclusion the TDS and EC in the groundwater in these locations.Keywords: Determination, Heavy metal, Atomic absorption, Groundwater wells.